The Coffee Bean a simple lesson to create positive change - Gordon, Jon. (New Jersey Wiley, 2019)
The Coffee Bean is an inspiring tale that follows Abe, a young man filled with stress and fear as he faces challenges and pressure at school and home. One day after class, his teacher shares with him the life-changing lesson of the coffee bean, and this powerful message changes the way he thinks, acts, and sees the world. Abe discovers that instead of letting his environment change him for the worse, he can transform any environment he is in for the better. Equipped with this transformational truth, Abe embarks on an inspirational journey to live his life like the coffee bean. Wherever his life takes him, from school, to the military, to the business world, Abe demonstrates how this simple lesson can unleash the unstoppable power within you.
Keywords: Change management